Calculation and design of directional antenna wideband irradiators for passive radar applications - Trần Minh Nghĩa; Lưu Đức Thọ; Phạm Khắc Lanh; Lương Văn Trình; Nguyễn Văn Việt (Journal of Military Science and Technology, 2022)
Recently, parabolic antennas are widely investigated and applied in military and civilian purposes. However, to ensure that the antenna system works in a wideband frequency, while still meeting the gain and high directivity in both planes is a complicated issue. In this paper, the authors present the results of research and design of an irradiator using ridged waveguides combined with dielectric lenses working in the frequency range 4-8 GHz (C band). The results of analysis of operating principles, calculations and simulations on CST 2019 software show that the antenna system has high gain and directivity in both planes over a wide frequency range, meeting the requirements operate on passive radars.